Application of an intangible asset valuation model using panel data for listed enterprises in Vietnam - Quan Minh Quoc Binh; Nguyen Minh Ha; Ngo Thi Huyen Trang (Investment Management & Financial Innovations, 2020)
Intangible assets play an important role in increasing the value of companies. The performance of companies increasingly depends on ideas, information, and professional services rather than tangible assets. The question of how to accurately measure intangible assets remains a challenge for many scientists. This study aims to measure intangible assets of 396 companies listed on Vietnam’s stock market between 2010 and 2014 using the panel data technique by Yamayuchi (2014). The estimation shows that intangible assets make up a large share of total assets of companies. In addition, construction, steel, building materials, mining, and food are sectors with high intangible assets in Vietnam. The study also finds a positive impact of intangible assets on improving company performance. The findings demonstrate the importance of investing in intangible assets, such as R&D, technology, advertising, and human resources, to increase the value of a company in the future.